PEMERTAHANAN BAHASA KAILI DIALEK LEDO DI DESA TINGGEDE KECEMATAN MARAWOLA KABUPATEN SIGI - Ferdiawan (KOLONI, 2022)
This study discusses the problem of maintaining the Kaili Ledo dialect in Tinggede village, Marawola district. This research is a qualitative research . The type of data used is data in the form of numbers calculated using statistical methods or the average formula and described in the form of words. Collecting data using observation techniques, questionnaires, and documentation. The instrument in this research is a questionnaire. Presentation of data, and drawing conclusions based on the results of research on maintaining the Ledo dialect language in the village of Tinggede are 1) The maintenance of the Ledo dialect kaili language in the family realm can be categorized as still strong and does not shift with a percentage of 40% which can be said to be stable and not displaced is said to be shifted in the anggaka. 30% percentage. 2) The maintenance of the Ledo dialect kaili language in the neighboring realm is categorized as still surviving with a percentage of 77.5% or above 50%, 3) The maintenance of the Ledo dialect kaili language in the public domain is categorized as still strong and does not shift with a total percentage of 48.33% or still above 40%. Keyword: Language Defense, Kaili dialect of Ledo, Tinggede Village